The Psychoactive Agent Crocin Can Regulate Hypothalamic-Pituitary-Adrenal Axis Activity - Asalgoo, Sara; Tat, Mahdi; Sahraei, Hedayat; Pirzad Jahromi, Gila (Frontiers in Neuroscience, 2017)
Post-traumatic stress disorder (PTSD) occurs following life-threatening events. The activity of the hypothalamic-pituitary-adrenal (HPA) axis, which serves as the first line of defense against stress, is dysfunctional in this disorder. The current study aimed to investigate the role of Crocin in normalizing HPA function in an animal model of PTSD induced by electric foot shock. Rats were treated with Crocin 5 min prior to stress induction. The stimulus was re-introduced after 21 days, and we measured individual behaviors such as sniffing, rearing, grooming, and freezing. Enzyme-linked immunosorbent assays were performed to measure plasma levels of Corticosterone. On day 28, after rats were weighed and sacrificed, the adrenal and thymus glands were removed and subjected to real-time polymerase chain reaction to quantify the gene expression of corticotrophin-releasing hormone (CRH), glucocorticoid receptor (GluR), and arginine vasopressin (AVP). Our results demonstrate that rats re-exposed to a stressor developed characteristic symptoms of PTSD, but these were attenuated by Crocin. Treated rats showed significant changes in CRH expression in the hypothalamus, GluR expression in the pituitary, plasma Corticosterone levels, and freezing behavior. Together, these findings suggest that Crocin can regulate HPA axis activity in PTSD. It may serve an appropriate treatment for subjects who experience a traumatic event.